Chain-mediated pathways of adults socioeconomic status affecting physical fitness in Macao: the role of motor skills and moderate to vigorous physical activity - Li, Mingzhe; Gao, Yibo; Zhang, Yanfeng; He, Jin; Chen, Xiaoxiao; Zhang, Hejie; Pan, Xiang; Jiang, Lupei; Hu, Haixia (Frontiers in Public Health, 2025)
To investigate the relationship between adults’ socioeconomic status and physical fitness, and the chain mediation effects of motor skills and moderate to vigorous physical activity on it. Based on the 2020 Macao Special Administrative Region Citizen’s Physical Fitness and Health Surveillance data, this study was conducted with 3,695 adults aged 20–59 years, and the data were analyzed using SPSS 29.0 software. The findings showed that (1) family socioeconomic status was positively correlated with physical fitness (p < 0.01); (2) motor skills and moderate-to vigorous physical activity mediated the above relationship, and the mediation consisted of three pathways: the separate mediation of motor skills, the separate mediation of moderate- -to vigorous physical activity, and the chain mediation of motor skills- moderate- -to vigorous physical activity. The findings reveal that family socioeconomic status can influence adult physical fitness through three pathways: motor skills, moderate to vigorous physical activity, and motor skills-moderate-to-vigorous physical activity chain mediation, which is of great theoretical significance for the improvement of adults’ physical fitness.